English: English - Ni Putu Dilia Dewi; Dian Rahmani Putri; Ida Ayu Maharani (RETORIKA: Jurnal Ilmu Bahasa, 2025)
The rapid advancement of digitalization presents challenges for English as a Foreign Language (EFL) students in developing speaking skills. The widespread use of online games often leads to passive behavior, limiting opportunities for oral communication practice. In an increasingly competitive world, proficient speaking skills combined with critical thinking are essential for effective communication and problem-solving. To address this gap, the card game "The Witchy" was developed as an innovative, interactive solution. The game provides an engaging platform for students to practice communication while enhancing critical thinking skills. This study adopted the Research and Development (R&D) model by Borg and Gall (1983) to design, test, and refine the game. Data were collected through classroom observations, pre-tests, and post-tests to evaluate improvements in fluency, vocabulary usage, and sentence structure.The findings revealed three key outcomes: (a) "The Witchy" positively impacted students’ speaking fluency, vocabulary, and sentence structure by offering dynamic and practical learning opportunities; (b) the game effectively promoted critical thinking and communication skills by requiring students to strategize and articulate their ideas; and (c) its motivational aspects fostered long-term engagement and active participation in English learning. Qualitative data, including classroom observations and student interactions, further supported the game’s effectiveness.This study demonstrates the potential of game-based learning in language education, offering a practical approach to improving speaking skills and fostering higher-order thinking in EFL students.